Analysis of Musyarakah and its Implementation at BMT Fadhilah Sentosa Bekonang - Aulia Azka Maulana; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
The mutual cooperation between the customer and the capital owner, namely Baitul Maal Wat Tamwil or BMT, is a partnership allowed by Allah SWT as long as there is no oppression towards either party in the partnership. "Musyarakah" itself is a form of cooperative agreement between two or more parties for a business endeavor in which each party contributes, and profits are shared equally while risks are collectively borne according to the agreements made by the parties involved. In this research, it can be analyzed that the Musyarakah practiced at BMT Fadhilah Santosa involves a management system where customers have full control, and BMT only provides motivation and input to advance the customer's business. Regarding profit-sharing calculations, BMT only determines the percentage of profit distribution, while the customers collectively decide the rest. The method used in this research is qualitative descriptive research with an inductive and categorical mindset. Based on the results of the research conducted, it can be analyzed that the Musyarakah financing at BMT Fadhilah Santosa is not fully in line with the fatwa issued by DSN-MUI. This is evident in the issues related to capital and loss-sharing.